Assisted Reproductive Technology Outcomes in Women with Normal Ovarian Response Receiving Recombinant Luteinizing Hormone/Human Menopausal Gonadotropin: An Observational Study - Liang Y; Hou X; Chen H; Yang R; Wang R; Mao R; Zhao J; Chen H; Cheng J (Dove Medical Press, 2024)
Yingxiu Liang,1 Xiaohong Hou,1 Haoying Chen,1 Ruqing Yang,1 Ruina Wang,1 Ruotong Mao,1 Junzhao Zhao,1 Hui Chen,2 Jing Cheng1 1Reproductive Center, Department of Obstetrics and Gynecology, The Second Affiliated Hospital and Yuying Children's Hospital of Wenzhou Medical University, Wenzhou, Zhejiang Province, 325088, People's Republic of China; 2School of Life Sciences, Faculty of Science, University of Technology Sydney, Ultimo, New South Wales, 2007, AustraliaCorrespondence: Jing Cheng, Reproductive Center, Department of Obstetrics and Gynecology, The Second Affiliated Hospital and Yuying Children's Hospital of Wenzhou Medical University, No. 306 Hualongqiao Road, Lucheng District, Wenzhou, Zhejiang Province, 325088, People's Republic of China, Tel +86 13780193700, Fax +86 57788002304, Email jingchengdoc_gyn@hotmail.com Hui Chen, Faculty of Science, University of Technology Sydney, No. 15 of Broadway, Ultimo, New South Wales, 2007, Australia, Tel/Fax +61 295141328, Email chenhuimind@sina.comObjective: Additive human menopausal gonadotropin (HMG)/recombinant luteinizing hormone (r-LH) to follicle-stimulating hormone (FSH) can improve pregnancy outcomes in patients with poor ovarian response during assisted reproductive procedures. However, their effects on patients with normal ovarian response during such procedures are unclear, which formed the aim of this study.Methods: This retrospective study enrolled 456 infertile women who underwent in vitro fertilization or intracytoplasmic sperm injection treatment. Group 1 received FSH; Group 2 received FSH+HMG/r-LH; Group 3 received FSH+HMG+r-LH.Results: The age and Body Mass Index were significantly greater in Group III. The endometrial thickness was greater in Groups II and III, suggesting better endometrial receptivity. Better pregnancy and birth outcomes were seen in Group 3. In sub-cohorts of women older than 32 years old or with overweight/obesity, pregnancy and birth outcomes were also much better in Group 3, albeit without statistical significance.Conclusion: The addition of both HMG and r-LH to FSH may improve the chance of infertile women with normal ovarian responses to have more success in having live birth babies, specifically in those over 32 years of age or with overweight/obese patients who typically face challenges in conceiving and sustaining a pregnancy.Keywords: in vitro fertilization, intracytoplasmic sperm injection, live birth rate, cumulative live birth rate